2021
DOI: 10.1371/journal.pone.0253934
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of clopyralid resistance in lawn burweed (Soliva sessilis)

Abstract: Soliva sessilis is a troublesome annual weed species in New Zealand turfgrass. This weed has been controlled selectively in New Zealand turfgrass for many years using pyridine herbicides such as clopyralid. However, in some golf courses, the continuous application of pyridine herbicides has resulted in the selection of S. sessilis populations that are resistant to these herbicides. This study focuses on a clopyralid-resistant population of S. sessilis collected from a golf course with a long history of clopyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…To confirm the individuals of R population were correctly identified as C. album , the psbA ‐ trnH and ITS regions were sequenced as these regions have been used as barcodes in plant taxonomy to identify plant species 28,29,33 . The results showed that the sequence from both R and S populations were identical to each other for the analysed psbA ‐ trnH and ITS regions, and also matched GenBank entries for C. album (e.g.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…To confirm the individuals of R population were correctly identified as C. album , the psbA ‐ trnH and ITS regions were sequenced as these regions have been used as barcodes in plant taxonomy to identify plant species 28,29,33 . The results showed that the sequence from both R and S populations were identical to each other for the analysed psbA ‐ trnH and ITS regions, and also matched GenBank entries for C. album (e.g.…”
Section: Resultsmentioning
confidence: 83%
“…abnormal leaf shape) manifested by the dicamba‐resistant C. album are likely to be associated with the mechanisms of resistance. Abnormalities in leaf shape and development have been documented in some other synthetic auxinic herbicide‐resistant weeds species such as Soliva sessilis Ruiz & Pav 33 . and Sinapis arvensis L 34 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…from New Zealand (14-fold). 54 The differences in the resistance level between C. album and B. scoparia from Montana and Soliva sessilis may be due to the presence of different resistance mechanisms.…”
Section: Dose-response Experimentsmentioning
confidence: 99%